SPECIFIC FAUNISTIC AND TAXONOMIC CHARACTERISTICS OF HELMINTHS OF SMALL HORNED CATTLE OF KARAKALPAKSTAN - Paluaniyazova D.A.; Dadayev S.D.; Beknayev U.A (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article presents information on the species composition of small horned cattle helminths, their systematic status, distribution, seasonal dynamics, extent of invasion and intensity of invasion in the conditions of Karakalpakstan. As a result of the study of helminths of small horned cattle of Karakalpakstan and the analysis of published literature, it was noted that 37 types of helminths parasitize small horned cattle. Of these, 34 species were found in sheep and 31 species in goats. The listed helminths belong to 25 genera, 16 families, 9 suborders, 8 families, 3 classes and 2 types of fauna. 26 types (70.2%) of 37 types of helminths parasitizing small horned cattle belong to nematodes, 8 types (21.6%) to cestodes and 3 types (8.1%) to trematodes